QUALITY OF LIFE FROM THE VIEWPOINT OF TWO BASIC COMPONENTS: THE ECONOMIC STANDARD AND SATISFACTION - ROXANA PLEŞA (Annals of the University of Petrosani: Economics)
In the present social/economic conditions of our country, the problem of objective analysis and research of the population’s everyday social life, of its wellbeing, of final consumption and possibilities of satisfying vital necessities, of the living standard and lifestyle, of the quality of life as a whole, becomes more and more present and significant. The notion of "quality of life" aims, on the one hand, the objective conditions in living individuals, and on the other hand, what they think about the individuals. In fact, in its essence, the quality of life implies a qualitative approach to social and human life, as assessed by experts and how it is experienced by the subjects.